2017
DOI: 10.1007/s11751-017-0283-9
|View full text |Cite
|
Sign up to set email alerts
|

Can experienced surgeons predict the additional value of a CT scan in patients with displaced intra-articular distal radius fractures?

Abstract: There are no clear guidelines when an additional CT scan should be obtained for the treatment of displaced intra-articular distal radius fractures (DRF). This study aimed to investigate whether surgeons can predict the usefulness of CT scans to facilitate choice of treatment plan and/or pre-operative planning for DRF. Four surgeons evaluated 51 patients with displaced DRF. The choice of treatment (operative or nonoperative) was based on conventional radiographs. Subsequently, the surgeons were asked whether th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…It has been found that experienced surgeons can predict the usefulness of CT scans for intra-articular displaced DRFs to decide on treatment, but for preoperative planning, the usefulness of CT scans is much harder to predict. 18 Although our study did not address potential reasons that address the causation between surgical experience with the likeliness of obtaining a CT and choosing an surgical intervention, several reasons may explain this effect. Experienced surgeons likely have greater exposure to evidence regarding the relative effectiveness of treatment strategies for DRFs.…”
Section: Discussionmentioning
confidence: 91%
“…It has been found that experienced surgeons can predict the usefulness of CT scans for intra-articular displaced DRFs to decide on treatment, but for preoperative planning, the usefulness of CT scans is much harder to predict. 18 Although our study did not address potential reasons that address the causation between surgical experience with the likeliness of obtaining a CT and choosing an surgical intervention, several reasons may explain this effect. Experienced surgeons likely have greater exposure to evidence regarding the relative effectiveness of treatment strategies for DRFs.…”
Section: Discussionmentioning
confidence: 91%
“…However, for preoperative planning, the usefulness of the computed tomography is much harder to predict. 11 das GraçasNascimento et al 30 also showed the relationship between surgeon experience and the need for a computed tomography. They found that computed tomography had minimal impact on the selection of treatment recommended by specialists and hand surgery residents but it was more useful for those less experienced in hand surgery.…”
Section: Discussionmentioning
confidence: 98%
“…As a result, the treatment plan was altered in 48% of the cases with an increase in recommendations for surgical treatment. 10 Kleinlugtenbelt et al 11 found that experienced surgeons can predict the usefulness of the computed tomography for the treatment of the intra-articular distal radius fractures. However, for preoperative planning, the usefulness of the computed tomography is much harder to predict.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation